Повторні операції за раку щитоподібної залози - Стернюк, Ю. М. (Clinical Endocrinology and Endocrine Surgery, 2017)
Reoperation for thyroid cancer need to consider patient, tumor and therapy related aspects as well as present diagnostic results. Reoperations for thyroid remnants, persistence of the primary tumor and lymph node metastasis (completion surgery) has to be distinguished from reoperation due to locoregional recurrence (primary tumor, lymph nodes). The primary surgical strategy should avoid the need for operation. The surgery for cure and limited surgery for cure are singed out. The optimal treatment is obtained by surgery for cure. The extent of reoperation is related to the extent of primary surgery, stage and distant metastasis. The timing and indication of differentiated thyroid carcinoma reoperation in an interdisciplinary multimodal treatment setting depend on diagnostic radioiodine scans and radioiodine therapy. Due to the biological features of the medullar cancer, the main accent of the therapy is pointed on the surgical treatment. Long-term, recurrence-free survival is achieved by sufficiently radical surgery with acceptable morbidity, including all additive or adjuvant treatment options.